Molecular adaptation to chronic antidepressant treatment: evidence for a more rapid response to the novel α₂-adrenoceptor antagonist/5-HT-noradrenaline reuptake inhibitor (SNRI), S35966, compared to the SNRI, venlafaxine. - Serres, F; Millan, M; Sharp, T (2012)
Evidence of early changes in neural plasticity may aid the prediction of rapid-onset antidepressant drugs. Here we compared the dual α₂-adrenoceptor antagonist/5-HT-noradrenaline reuptake inhibitor (SNRI), S35966, to the SNRI, venlafaxine, with regards to their effect on rat brain expression of a panel of neural plasticity-related genes: Arc, BDNF, and VGLUT1, as well as Homer1a and Shank1B (not studied previously). Abundance of mRNA was determined by in-situ hybridization in cortical and hippocampal regions 2 h and 16 h following drug administration for 14, 7 and 1 d. After 14 d, both S35966 and venlafaxine increased mRNA of all genes, including Homer1a and Shank1B, and effects were similarly time- and region-dependent. After 7 d, S35966 elevated Arc, Shank1B and BDNF mRNA, whereas venlafaxine increased Shank1B mRNA only. Finally, after 1 d (acute administration), S35966 increased Arc and Homer1a mRNA whereas venlafaxine had no effect on any gene examined. In summary, a 14-d course of treatment with S35966 or venlafaxine induced similar region- and time-dependent increases in expression of neural plasticity-related genes including Shank1B and Homer1a. Some genes responded earlier to S35966, suggesting that drugs with combined α₂-adrenoceptor antagonist/SNRI properties may elicit more rapid changes in markers of neural plasticity than a SNRI alone.